Bacterial LuxR solos have evolved to respond to different molecules including signals from plants - Patel, Hitendra K.; Suárez-Moreno, Zulma R.; Degrassi, Giuliano; Subramoni, Sujatha; Gonzalez, Juan F.; Venturi, Vittorio (Frontiers in Plant Science, 2013)
A future challenge will be understanding the extensive communication that most likely takes place in bacterial interspecies and interkingdom signaling between plants and bacteria. A major bacterial inter-cellular signaling system in Gram-negative bacteria is LuxI/R quorum sensing (QS) based on the production (via the LuxI-family proteins) and detection (via the LuxR-family proteins) of N-acyl homoserine lactones (AHLs) signaling molecules. LuxR proteins which have the same modular structure of QS LuxRs but are devoid of a cognate LuxI AHL synthase are called solos. LuxR solos have been shown to be responsible to respond to exogenous AHLs produced by neighboring cells as well endogenously produced AHLs. It is now also evident that some LuxR proteins have evolved from the ability to binding AHLs and respond to other molecules/signals. For example, recent research has shown that a sub-family of LuxR solos responds to small molecules produced by plants. This indicates the presence of a uni-directional interkingdom signaling system occurring from plants to bacteria. In addition LuxR solos have now been also implicated to respond to endogenously produced signals which are not AHLs. In this Mini Review article we will discuss current trends and implications of the role of LuxR solos in bacterial responses to other signals using proteins related to AHL quorum sensing systems.